Functional Nanocarriers for Delivering Itraconazole Against Fungal Intracellular Infections - Mejía, Susana P.; Sánchez, Arturo; Vásquez, Viviana; Orozco, Jahir (Frontiers in Pharmacology, 2021)
Infectious diseases caused by intracellular microorganisms represent a significant challenge in medical care due to interactions among drugs during coinfections and the development of resistance in microorganisms, limiting existing therapies. This work reports on itraconazole (ITZ) encapsulated into functional polymeric nanoparticles (NPs) for their targeted and controlled release into macrophages to fight intracellular infections. NPs are based on poly(lactic acid-co-glycolic acid) (PLGA) polymers of different compositions, molecular weight and lactic acid: glycolic acid ratio. They were self-assembled by the high-energy nanoemulsion method and characterized by transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR) and differential scanning calorimetry (DSC). It was studied how the polymer: drug ratio, changes in the aqueous phase pH, and type and concentration of surfactant affected nanocarriers' formation, drug loading capacity (DLC) and encapsulation efficiency (EE). Results showed that DLC and EE went to 6.7 and 80 %, respectively, by lowering the pH to 5.0 and using a mixture of surfactants. Optimized formulation showed an initial immediate ITZ-release, followed by a prolonged release phase that fitted better with a Fickian-diffusion kinetic model and high stability at 4 °C and 37 °C. NPs functionalized by the adsorption and carbodiimide methods gave different efficiency, being the carbodiimide approach more efficient, stable and reproducible. Furthermore, linking F4/80 and mannose to the NPs demonstrated to increase macrophages J774A.1 uptake. Overall, in vitro assays showed the nanosystem's efficacy to eliminate the Histoplasma capsulatum fungus and pave the way to design highly efficient nanocarriers for drug delivery against intracellular infections.